An Individual Counseling Model Based on the Health Belief Model Improves Support for Adolescent Victims of Bullying - Novi Astri Ani; Wahyu Endang Setyowati; Dwi Heppy; Iskim Luthfa (FORIKES, 2026)
Bullying is a form of chronic social stress that has significant adverse effects on adolescent mental health, including an increased risk of depression, anxiety, psychological distress, post-traumatic stress disorder, and the development of maladaptive self-beliefs. The literature indicates that the impact of bullying victimization is not solely determined by the frequency and intensity of bullying experiences, but also by cognitive processes such as threat perception, self-meaning, resilience, and self-efficacy. This review aims to formulate a conceptual framework for individual counseling based on the Health Belief Model (HBM) for adolescents who have experienced bullying through a synthesis of recent empirical findings. A narrative literature review design was employed, with articles retrieved from Scopus, PubMed, ScienceDirect, and Google Scholar published between 2019 and 2025. Thematic analysis was conducted to identify patterns in the psychological impacts of bullying, the role of protective factors, and the relevance of cognitive-based interventions. The findings indicate that bullying victimization contributes to the internalization of negative cognitive schemas that influence coping behaviors and help-seeking processes. Resilience and self-efficacy were identified as important mediators and moderators in the relationship between bullying and mental health outcomes. The Health Belief Model provides a relevant conceptual basis for individual counseling by emphasizing perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-efficacy.Keywords: bullying; adolescents; mental health; individual counseling; health belief model